Processing Speed and Executive Abilities in Children with Phenylketonuria - Janos, Alicia L. (2012)
OBJECTIVE: Phenylketonuria (PKU) is a hereditary metabolic disorder that often results in neuropsychological impairment, even in individuals treated early and continuously. This study was conducted to examine processing speed, variability in processing speed, and the relationship between processing speed variables and executive abilities in children with early- and continuously-treated PKU. METHOD: Participants were 42 children with PKU and 81 typically-developing children from 7 to 18 years of age. Children completed three computerized reaction time (RT) tasks (simple reaction time, go/no-go, stimulus-response compatibility) and seven tasks assessing executive abilities (working memory, inhibitory control, strategic processing). RESULTS: Performance of children with PKU was significantly slower and more variable than that of controls across the three tasks administered. When age was considered, it was shown that processing speed improved with age to a comparable degree for both groups. Variability in processing speed, however, decreased more with age for the PKU than control group, reflecting the fact that variability in younger, but not older, children with PKU was greater than that of controls. With regard to executive abilities, processing speed and variability contributed to performance on most, but not all, executive tasks; and after controlling for processing speed and variability, executive impairments were still identified in working memory and inhibitory control (not strategic processing). CONCLUSIONS: These findings indicate that information processing is slower and less efficient in children with PKU. In addition, processing speed and variability contribute to some, but not all, of the impairments in executive abilities observed in children with PKU.